1992
DOI: 10.2134/jpa1992.0431
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Comparison of Subsurface Microirrigation with Center Pivot Sprinkler Irrigation

Abstract: Simulation is used to compare water use, yields, and the relative profitably of fixed and towable center‐pivot sprinkler irrigation and subsurface microirrigation for a corn (Zea mays L.) and soybean (Glycine max L.) rotation. Mean water use is somewhat lower on corn for microirrigation compared to sprinkler irrigation while water use differs little on soybean. Yield responses to irrigation differ little between the two systems. Relative profitability of systems depends on size. At 75 acres, subsurface microir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 2 publications
2
28
0
Order By: Relevance
“…In a related publication, Mitchell and Tilmon (1982) suggested SDI as a good, economical, alternative irrigation system for small farmers in the U.S. This is because the components of SDI systems can be easily and economically designed to accommodate the field size (Bosch et al, 1992;O'Brien et al, 1998). Several early SDI corn studies (1989 to 1999) from Kansas were discussed by Lamm and Trooien (2003).…”
Section: Cornmentioning
confidence: 99%
“…In a related publication, Mitchell and Tilmon (1982) suggested SDI as a good, economical, alternative irrigation system for small farmers in the U.S. This is because the components of SDI systems can be easily and economically designed to accommodate the field size (Bosch et al, 1992;O'Brien et al, 1998). Several early SDI corn studies (1989 to 1999) from Kansas were discussed by Lamm and Trooien (2003).…”
Section: Cornmentioning
confidence: 99%
“…O'Brien et al 1998 (14) suggests that sub‐surface drip systems are more economical than overhead sprinkler systems in fields smaller than 65 acres. Sub‐surface drip systems are more efficient at covering irregularly shaped field which would not be totally covered with overhead irrigation systems (1). Previous research in Virginia, North Carolina, and Georgia demonstrated a positive response to sub‐surface drip irrigation in both cotton and peanut ( Arachis hypogaea L.) (1,7,8,11,13,18).…”
Section: Introductionmentioning
confidence: 99%
“…Previous economic research reported that subsurface drip systems (SSDI) would be more profitable for small areas (<50 acre) because of their lower per‐acre investment and lower pumping costs compared with fixed or towable center‐pivot systems (2,21). Other research showed that as field size decreased, SSDI net returns increased (21).…”
Section: Introductionmentioning
confidence: 99%
“…Other research showed that as field size decreased, SSDI net returns increased (21). It was also noted that results were sensitive to SSDI life (less than 10 years), as well as changes in crop price and system components (2,23). Drip irrigation would be an acceptable choice for irregularly shaped fields where a full‐circle irrigation system cannot be installed.…”
Section: Introductionmentioning
confidence: 99%